International Legal and Philosophical Aspects of the New Protection Concept of the Common Heritage of Mankind: Philosophical and Legal Worldview - Радзівілл, Олександр Анатолійович; Радзівілл, О. А.; Радзивилл, Александр Анатольевич; Radzivill, Oleksandr A.; Шульженко, Федір Пилипович; Шульженко, Ф. П.; Шульженко, Федор Филиппович; Shulzhenko, Fedir P.; Голосніченко, Іван Пантелійович; Голосніченко, І. П.; Голосниченко, Иван Пантелеевич; Holosnichenko, Ivan P.; et al. (Khachatur Abovyan Armenian State Pedagogical University, 2020)
The article is devoted to the systematize the characteristics of objects of the common heritage of mankind, to study the historical origins and connections of the concept of the common heritage of mankind with other legal categories and worldview systems, to determine the prospects of application of the concept in its legal and worldview aspects. The work is based on a set of approaches united in sociological legal consciousness, primarily historical, communicative and psychological ones, and on the methodological basis of I. Kant’s philosophy. The concept of the common heritage of mankind in the context of trans-historical development of social consciousness as an important system-making factor of societies of macro-level scales for the first time is investigated in the research. Mankind should return to its social consciousness an intersubjective relation to its planetary natural environment, that is, its inclusion in its multilevel diversity and recognition of its “subjectivity”, if not in a legal sense, then in the awareness of its complexity, self-regulatory properties, the need for its constant cognition in feedback mode – this idea should be the main new concept of protection of the common heritage of mankind.

Стаття присвячена систематизації характеристик об'єктів спільної спадщини людства, вивченню історичних витоків та зв'язків концепції спільної спадщини людства з іншими правовими категоріями та світоглядними системами, визначенню перспектив застосування концепції в її правовому та світоглядному аспектах. Робота базується на комплексі підходів, об’єднаних у соціологічній правосвідомості, насамперед історичному, комунікативному та психологічному, та на методологічних засадах філософії І. Канта. У дослідженні вперше досліджено концепцію спільної спадщини людства в контексті доісторичного розвитку суспільної свідомості як важливого системотворчого чинника суспільств макрорівневих масштабів. Людство повинно повернути інтерсуб’єктивне відношення у своїй соціальній свідомості до свого планетарного природного середовища, тобто включити його у багаторівневе різноманіття та визнання своєї „суб’єктивності”, якщо не в юридичному сенсі, то в усвідомленні своєї складності, регуляторних властивостей, необхідності його постійного пізнання в режимі зворотного зв'язку - ця ідея повинна стати головною новою концепцією захисту спільної спадщини людства.

Статья посвящена систематизации характеристики объектов общего наследия человечества, изучению исторических веток и связей концепций общего наследия человечества с другими правовыми категориями и мировыми системами, определено перспективное применение концепции в ее правовом и мировом аспектах. Работа базируется на комплексных подходах, объединенных в социологическое правосознание, предыдущем историческом, коммуникативном и психологическом, и на методологических принципах философии Канта. В работе впервые исследована концепция общего наследия человечества в контексте доисторического развития общественного сознания как нового системного создания общественных макроуровневых масштабов. Человечество должно повернуть интерсубьективное отношение в своем социальном сознании к своей планетарной природной среде, то есть включить его в многоуровневое разнообразие и признание своей "субъективности", если не в юридическом смысле, то в осознании своей сложности, регуляторных свойств, необходимости его постоянного познания в режиме обратной связи - эта идея должна стать главной новой концепцией защиты общего наследия человечества.
Radzivill O. International Legal and Philosophical Aspects of the New Protection Concept of the Common Heritage of Mankind: Philosophical and Legal Worldview / O. Radzivill, F. Shulzhenko, I. Golosnichenko, V. Solopenko, Y. Pyvovar // WISDOM. – V. 15(2). – Khachatur Abovyan Armenian State Pedagogical University, 2020. – P. 153-174.
Keywords: protection of human rights; common heritage of mankind; international law; air and space law; sea law; philosofical worldview; legal existence; захист прав людини; спільна спадщина людства; міжнародне право; повітряне та космічне право; морське право; філософський світогляд; правове існування; защита прав человека; общее наследие человечества; международное право; воздушное и космическое право; морское право; философское мировоззрение; правовое существование; Research Subject Categories::LAW/JURISPRUDENCE